أحكام التخارج من التركة في الفقه الإسلامي - اللبان، محمد فؤاد رشاد (جامعة الأزهر - کلية الدراسات الإسلامية والعربية للبنات بالإسكندرية, 2024)
من النزاعات التي قد تحدث بين الورثة التنازع بينهم في قسمة التركة ورغبة البعض منهم في الاستئثار بجزء مميز منها أو إرادة بعض الورثة قصر التركة عليهم؛ فكان التخارج بين الورثة أفضل وسيلة لغلق باب التنازع بين الورثة، وحتى يقع التخارج صحيحا موافقا للشرع لابد من توافر شروطه وانتفاء موانعه، كما أن للتخارج أشكال وأحوال تؤثر في صحته، وقد يكون بالتركة وارث غير محقق الوجود كالحمل والمفقود وحقيقة صحة التخارج في هذه الحالة، فقد قمت بالبحث والدراسة لجميع هذه المسائل بعرض أقوال الفقهاء والاستدلال لها والترجيح ثم تناولت الأحوال التي ينتقض فيها التخارج. -يوصى بأن يضاف لقانون المواريث ما ينظم التخارج بطريقة أوسع تفصيلا بحيث يدخل فيه ما يتعلق بضرورة توثيق عقد التخارج، وتنظيم ما يتعلق بالتخارج بالتقدير كالتخارج في التركة التي يوجد بها حمل أو مفقود. -أنه لا تخارج في التركة المحملة بالدين إلا بعد سداده فلا تركة إلا بعد سداد الديون، وكذلك التركة المحملة بالوصية فلا يحصل فيها تخارج إلا بعد أداء الوصية. One of the conflicts that may occur between heirs is the conflict between them in dividing the inheritance and the desire of some of them to take a distinct part of it or the will of some heirs to limit the estate to them. The reconciliation between heirs is the best way to end the dispute between heirs in order for an exit to be valid in accordance with the law, its conditions must be met and its inhibitions no longer exist. reconciliation also has forms and conditions affecting its validity, and it may have an unrealized legacy such as pregnancy, loss and the fact that proves the case in which reconciliation is valid, I have searched and studied all these issues by presenting the opinions of the scholars, inferring them, comparing them and then dealing with the situations in which the reconciliation is abating. It is recommended that the Law on Inheritance be added to regulate the reconciliation in a more detailed manner to include the need for documentation of the contract of reconciliation and the regulation of the exclusion in appreciation, such as reconciling the inheritance where a pregnancy is or is missing. It may pay the debt of inheritance to can hold the reconciliation, it is not left until after payment of the debts, as well as the estate loaded with the will, in which no reconciliation takes place until after performance of the will.
Keywords: علم أصول الفقه -- قانون المواريث -- عقود التخارج